Dinamika Penyelesaian Sengketa Tanah Hak Ulayat Masyarakat Adat Dikabupaten Fakfak Provinsi Papua Barat - Grace Angelia Soenartho; Amad Sudiro (LPPM Universitas Ekasakti Padang, 2023)
This research delves into the dynamics of resolving land disputes over customary rights among indigenous communities in Fakfak Regency, West Papua Province. The study addresses the historical context of customary rights in Fakfak, examining the growth and development of land disputes within this framework. Theoretical exploration encompasses the principles and concepts of customary rights within indigenous societies, accompanied by an analysis of relevant legal foundations and regulations in Papua Barat. Employing a multidisciplinary approach, the research scrutinizes common causes of land disputes and evaluates the role of social and political conflicts in these disputes. The study investigates various dispute resolution methods, assessing their advantages and shortcomings. Special attention is given to the active participation of indigenous communities in the resolution process, exploring factors influencing their involvement. Cultural and social dynamics affecting land dispute resolution are analyzed, identifying challenges and external factors complicating the process. The research concludes with recommendations for improvement, offering insights into effective dispute resolution strategies. Case studies from Fakfak Regency provide concrete examples, contributing to a comprehensive understanding of the subject. The findings have implications for policies and practices related to customary land dispute resolution.